Niveles de actividad física de los docentes de planta de la Universidad Del Quindío, a través del cuestionario IPAQ (2019)
The aim of this study was to determine the level of physical activity of the professors at University of Quindío through an IPAQ questionnaire. This research was developed under a quantitative approach, descriptive type, non-experimental and cross-sectional design. The population was 190 professors who belong to the University of Quindío’s teaching staff, with ages varying from 18 to 69 years old, with an average age of 50.63 years with a standard deviation of 9.44. The International Physical Activity Questionnaire (IPAQ) short version, was applied to determine the levels of physical activity of the population. The results indicated that more than half of the teaching population is classified as physically active. Also, that the predominant social status was for 4, and finally that in terms of sex, a greater proportion of the population was male. This led us to conclude that the professors of the University of Quindío presented high activity levels in comparison with the previous and different studies found, in which the population was below 50% regarding the practice of physical activity.